Production of Biomass Crops Using Biowastes on Low‐Fertility Soil: 2. Effect of Biowastes on Nitrogen Transformation Processes. Issue 6 (1st November 2016) - Esperschuetz, J.; Bulman, S.; Anderson, C.; Lense, O.; Horswell, J.; Dickinson, N.; Robinson, B. H.
Abstract : Increasing production of biowastes, particularly biosolids (sewage sludge), requires sustainable management strategies for their disposal. Biosolids can contain high concentrations of nutrients; hence, land application can have positive effects on plant growth and soil fertility, especially when applied to degraded soils. However, high rates of biosolids application may result in excessive nitrogen (N) leaching, which can be mitigated by blending biosolids with other biowastes, such as sawdust. We aimed to determine the effects of biosolids and sawdust on growth and N uptake by sorghum, rapeseed, and ryegrass as well as N losses via leaching. Plants were grown in a greenhouse over a 5‐mo period in a low‐fertility soil amended with biosolids (1250 kg N ha −1 ), biosolids‐sawdust (0.5:1), or urea (200 kg N ha −1 ). Urea application increased biomass production of sorghum and ryegrass but proved insufficient for rapeseed on low‐fertility soil. Biosolids application increased plant N concentrations in ryegrass and rapeseed and increased N uptake into the seeds of sorghum, increasing seed quality. Biosolids application did result in lower N leaching compared with urea, irrespective of plant species, and N leaching was unaffected by mixing the biosolids with sawdust. There was an indication of biological nitrification inhibition in the rhizosphere of sorghum. Rapeseed had similar growth and N uptake into biomass in biosolids and biosolids‐sawdust treatments and hence was the most promising species with regard to recycling fresh sawdust in combination with high rates of biosolids on low‐fertility soil. Core Ideas: Mixing sawdust with biosolids did not reduce NO3 − leaching irrespective of plant species. Compared with urea, biosolids application did not result in higher N loss via leaching. Results indicated biological nitrification inhibition of sorghum.